Risk management and financial stability in the Polish public hospitals: The moderating effect of the stakeholders' engagement in the decision-making - Aldona Fraczkiewicz-Wronka; Tomasz Ingram; Karolina Szymaniec-Mlicka; Piotr Tworek (Risks, 2021)
Public healthcare organizations usually operate under significant financial strain and frequently strive for survival. Thus, in most cases, financial stability is a "holy grail" of public healthcare organizations in general and hospitals in particular. The financial stability itself is partly dependent upon the ability to manage risk associated with hospital actions. In the paper, we seek to address the question related to the moderating role of stakeholders' engagement in the relationship between risk management practices and a hospital's financial stability. To answer this question, we designed and carried out empirical research on a sample of 103 out of 274 Polish public hospitals operating at the first-level (closest to the patient). Results show that risk management practices are positively related to financial stability. Hospitals with well-developed risk management practices are better prepared and find appropriate answers to threats, helping them attain financial stability. We also found that stakeholder engagement acts as a moderator of the relationship between risk management practices and financial stability. Research results indicate that with more sophisticated risk management practices, stakeholder engagement in decision-making leads to statistically lower financial stability. On the other hand, high levels of stakeholders' engagement help when risk management practices are underdeveloped.
Keywords: 330; financial stability; Poland; public hospitals; public management; risk management; stakeholders’ engagement; survey research